LOI: the methodological guide that improves terminal efficiency - Alcántara Gutiérrez, María Esther; Ramírez Martínez, Mireya (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The general objective of this article is to base the map of functions of the research teacher -whom the authors have designated as LOI-, in order to serve as a basis for the generation of the standard of competence in the teaching of the methodology to ensure the meaningful learning from the constructivist approach. The study presents the results achieved in two conglomerates, one that receives the traditional methodological teaching and the other that considers the new approach established in the Map of LOI functions, and its impact on terminal efficiency and the reduction of university desertion.